Zinc negative electrode modifier with zinc-philic-hydrophobic double-interface protective layer, modification method and application of zinc negative electrode modifier
A zincophilic-hydrophobic bifunctional silane interface layer addresses zinc dendrite and HER issues in zinc-ion batteries, enhancing cycle life and electrochemical performance by regulating zinc ion flux and solvation, achieving stable and efficient zinc-ion battery operation.
Patent Information
- Application Number
- CN202411200051.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-13
AI Technical Summary
Zinc-ion batteries face issues such as zinc dendrite formation, hydrogen evolution reaction (HER), and chemical passivation, leading to low coulombic efficiency, battery short circuits, and reduced cycle performance, which hinder their large-scale application.
A zincophilic-hydrophobic bifunctional silane interface layer is applied to the zinc negative electrode, regulating zinc ion flux and inhibiting HER by controlling the solvation structure, resulting in a uniform deposition and stable SEI film formation.
The modified electrode inhibits zinc dendrite growth, improves cycle life, and enhances electrochemical performance, with stable cycling at high current densities and high specific capacity, demonstrating improved battery stability and efficiency.
Smart Images

Figure CN119133453A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a zinc negative electrode modifier with a zinc-philic-hydrophobic double interface protective layer, a modification method and application thereof, and belongs to the technical field of zinc ion batteries. Background Art
[0002] For hundreds of years, especially after the third scientific and technological revolution, the high-quality and rapid development of human industrial civilization has continuously increased the demand for electricity supply. However, the reserves of fossil fuels such as coal, oil, and natural gas are limited and are deeply restricted by geographical factors, becoming an obstacle to the future development of industry and technology. In addition, fossil fuels release a large amount of harmful byproducts and greenhouse gases during combustion, such as SO2, NO X , CO2 and other gases and the inhalable particles and fine particles emitted with these gases, these industrial "three wastes" will cause continuous pollution of water, air and soil, and aggravate global warming. In contrast, renewable energy such as solar energy, wind energy, biomass energy, geothermal energy, etc. have the advantages of being green, abundant and widely distributed, and are an important support for promoting energy security and accelerating green and low-carbon transformation.
[0003] However, the sources of renewable energy are unstable, with large peak-to-valley differences, which causes large fluctuations in the output power of the energy, which can easily cause damage to the power grid. It also faces problems such as the mismatch between the peak power generation and the peak power consumption. In addition, the uneven spatial distribution of renewable energy also causes part of the electricity generated by the power generation side to be lost during the transmission process, which brings additional challenges.
[0004] In order to solve these problems, energy conversion and storage systems are becoming increasingly important. These systems can convert difficult-to-store electrical energy into chemical energy, gravitational potential energy or kinetic energy, and play a role in reshaping the voltage, current and power of power generation to mitigate the impact of power generation or power grid power on power facilities. By changing the production, transmission and use patterns of electricity, these systems can significantly increase the level of acceptance of clean energy, support the development of distributed power and microgrids, and become a key technology to promote the transition from fossil energy to renewable energy.
[0005] Batteries and electrochemical devices are the most convenient energy storage devices, and are widely used in 3C electronic devices, electrochemical energy storage, distributed energy storage, power batteries, military industry and other fields. Since the launch of the first commercial lithium-ion battery (LIB) system in the 1990s, after more than 30 years of development, lithium-ion batteries have been developed on a large scale due to their high specific energy, good cycle performance and mature process routes. In most fields, they have gradually replaced the previously widely used secondary electrochemical systems such as nickel-hydrogen batteries. At present, rechargeable lithium-ion batteries dominate the portable electronic product market and are fully used in various fields of daily life. However, the reserves of lithium in the earth's crust are limited, and the cost of batteries is high. At the same time, the uneven distribution of resources such as lithium and cobalt also makes it risky as a strategic war preparedness resource. These factors limit its application and development in large-scale energy storage.
[0006] Zinc-ion batteries are a typical representative of the new generation of electrochemical energy storage devices. Unlike traditional lithium-ion batteries, its positive electrode uses a zinc ion storage electrode, mainly manganese-based and vanadium-based materials. At present, there are many reports of positive electrode materials such as Prussian blue analogs, conversion compounds, sulfur elements, and halogen elements at home and abroad; while the negative electrode mostly uses zinc metal. During the charge and discharge process of zinc-ion batteries, energy is stored and released through the reversible stripping / plating of zinc at the negative electrode and the insertion / deinsertion of zinc ions at the positive electrode. Compared with lithium-ion battery systems, zinc-ion batteries have the following advantages: (1) Low price, safety and stability: Zinc metal is naturally abundant (about 300 times that of Li), so it is cheap and easy to process; at the same time, the cost of aqueous electrolytes is much lower than that of organic systems, which helps to reduce the cost of battery manufacturing. In addition, aqueous electrolytes have high chemical compatibility with zinc elements, which further enhances manufacturing safety and prolongs the service life of the battery; (2) Superior performance indicators: The ionic conductivity of aqueous electrolytes (about 0.1S cm -1 ) is significantly higher than that of organic system (<10 -2 S cm -1 ), providing excellent rate performance for the battery. Zinc metal has a relatively low redox potential (-0.76V vs SHE), a high mass specific capacity (820mAh g -1 ) and extremely high volumetric capacity (5,854 mAh cm -3), making it an ideal choice for high-energy-density rechargeable secondary batteries; (3) Wide application scenarios: Zinc-ion batteries have strong safety and intrinsic biocompatibility, and are suitable for a variety of application scenarios, such as wearable electronic devices, and have great application potential; (4) Environmental friendliness: Compared with organic electrolytes, aqueous electrolytes significantly reduce pollution during battery assembly. In addition, the mining, refining and recycling technologies of zinc metal have become more mature than those of lithium metal, which helps to reduce the environmental load of zinc throughout its life cycle. Therefore, in recent years, aqueous zinc-ion batteries have gradually become a research hotspot in the field of green secondary batteries.
[0007] Zinc-ion batteries are considered to be one of the most promising high-energy storage devices with broad application prospects. However, zinc metal is a relatively active metal with intrinsic electrochemical reaction activity and thermodynamic reaction tendency. During the battery cycle, it faces serious problems such as zinc dendrite formation, hydrogen evolution reaction (HER) and chemical passivation, which directly lead to low coulombic efficiency and battery short circuit, causing the battery's cycle performance to decline, affecting the large-scale application of zinc-ion batteries. In addition, the interaction of these problems further exacerbates their negative impact on zinc-ion batteries.
[0008] The zinc deposition process can be divided into four consecutive processes: Zn 2+ Mass transfer, Zn 2+ Desolvation, charge transfer, and zinc nucleation and growth. The intrinsic unevenness on the electrode surface leads to an uneven initial charge distribution, while the "tip effect" of electrons causes zinc ions to preferentially deposit in areas with higher electric field intensity and form micro-protrusions. As the cycle progresses, the tip effect is further aggravated, and these dendrites gradually grow on the surface of the zinc negative electrode, further aggravating the unevenness of the electric field and the morphology of the electrode surface. Ultimately, the disorderly growing zinc dendrites will penetrate the diaphragm, causing the battery to short-circuit and eventually fail. In addition, untreated zinc foil usually does not have a horizontal deposition morphology during the cycle, and usually forms a loose, non-dense structure that is easily separated from the negative electrode surface, forming the so-called "dead zinc", resulting in a significant loss of active Zn species, thereby reducing the battery's cycle performance and Coulombic efficiency.
[0009] In addition, aqueous zinc-ion batteries also face the HER problem. From the Pourbaix diagram of the zinc-water binary system, we can see that due to the Zn 2+ The redox potential of Zn (-0.76V, vs. SHE) is always lower than the hydrogen evolution potential of water, which makes the zinc negative electrode tend to spontaneously generate hydrogen in electrolytes of various pH values. The generation of hydrogen will not only reduce the Coulomb efficiency of the battery, but also cause problems such as battery bloating and rupture, electrolyte leakage and drying, which will seriously affect the battery's cycle performance.
[0010] The chemical passivation reaction of the zinc anode also has a significant impact on the degradation of battery performance. In neutral or weakly acidic electrolytes, HER leads to OH - The formation of an ion concentration gradient on the surface of the zinc anode increases the pH value of the near-surface region of the zinc anode. The weakly alkaline electrolyte in these regions reacts with zinc ions to form insulating basic zinc sulfate (Zn4SO4(OH)6·xH2O) and other species on the surface of the anode, resulting in chemical passivation of the surface:
[0011]
[0012] The HER-zinc negative electrode chemical corrosion reaction competes with the zinc deposition reaction. The growth of zinc dendrites expands the active surface area of the zinc electrode, further exacerbating the occurrence of hydrogen evolution reaction and corrosion. Therefore, the interaction between zinc dendrite formation, hydrogen evolution reaction and chemical passivation jointly has a negative impact on the zinc electrode surface.
[0013] In response to these problems, researchers at home and abroad have extensively studied the reaction mechanism of zinc anode in electrochemical cycles and proposed modification strategies, focusing on surface modification, structural design, electrolyte regulation and diaphragm design. Among them, the surface modification of metal zinc anode has received extensive attention from researchers because of its easy manipulation. However, so far, researchers have not reached a consensus on the effect of the wettability of the zinc anode surface after modification by zinc sulfate electrolyte. Some researchers believe that the hydrophilic modification layer helps to smooth the zinc ion deposition flux and achieve uniform zinc ion deposition; others believe that the hydrophobic modification layer can promote the desolvation of hydrated zinc ions, thereby inhibiting the HER process. One possible explanation is that the "hydrophilicity" index often mentioned by researchers cannot accurately reflect the affinity of (hydrated) zinc ions with the anode at the electrode-electrolyte interface side, and it should be replaced by a more reasonable "zinc affinity" index to characterize the affinity of zinc ions with the zinc anode. When the interface modification layer mainly acts to improve the zinc deposition flux and make it uniform, thereby inhibiting the formation of zinc dendrites, the zinc-philic interface modification layer may have better performance; if the mechanism of action of the interface modification layer is to inhibit the hydrogen evolution reaction between the zinc negative electrode and the electrolyte, then the hydrophobic modification layer may help regulate the dehydration of hydrated zinc ions, thereby avoiding direct contact between the zinc negative electrode and water molecules to improve the electrochemical performance of the zinc negative electrode. However, it should be noted that if no special design is performed, the zinc-philic interface layer often also has hydrophilic properties, which may lead to enhanced corrosion reactions and thus be detrimental to the cycle stability of the battery. In view of this, researchers have balanced the zinc-philic and hydrophobic properties in two dimensions: (1) by structurally designing the modification layer on the surface of the zinc negative electrode, using the different properties of different molecules to balance the zinc-philic and hydrophobic properties; (2) by precisely controlling the thickness and other properties of the modification layer, the unfavorable properties of zinc-philic properties such as increased resistance and poor kinetics caused by thick hydrophobic interface modification layers can be avoided. Summary of the invention
[0014] Based on this, a zincophilic-hydrophobic artificial bisilane interface layer is designed in the present invention. A high-performance modified zinc negative electrode is prepared by spraying zincophilic-hydrophobic bifunctional silanes on the exposed metallic zinc surface in sequence. By controlling the spraying time, the thickness of the coating can be precisely controlled. In the bifunctional modification layer, the inner zincophilic silane can regulate the zinc ion flux and promote the uniform deposition of zinc ions; while the outer hydrophobic silane can regulate the solvation structure of zinc ions and prevent the hydrogen evolution reaction caused by direct contact between hydrated zinc ions and the zinc negative electrode. Finally, the prepared composite negative electrode has good performance at different current densities (1 mA cm -2 and 5mA cm -2) showed low overpotential in symmetrical cells and cycled stably for more than 1000 hours. In order to verify the practical application potential, the button-type full battery prepared with VO2 positive electrode can cycle stably for 1900 weeks and maintain 120mAh g -1 The discharge specific capacity shows excellent cycle performance.
[0015] To achieve the purpose of the present invention, the following technical solutions are provided.
[0016] A method for modifying a negative electrode of a zinc ion battery, the method comprising the following steps:
[0017] (1) preparing modification solution A: anhydrous ethanol + deionized water + zincophilic silane + zinc trifluoromethanesulfonate; B: anhydrous ethanol + deionized water + hydrophobic silane + zinc trifluoromethanesulfonate, and magnetically stirring the mixed modification solutions A and B for 6 hours to obtain a uniform solution;
[0018] (2) Modification liquid spraying: Liquid A and Liquid B are sprayed onto the surface of the pretreated zinc negative electrode in sequence. After each coating is sprayed, it is dried at room temperature for 30 minutes and then dried in a high-temperature drying oven for 6 hours.
[0019] Preferably, the zinc-philic silane is one or more of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-aminopropylmethyldiethoxysilane, β-cyanoethyltriethoxysilane, γ-cyanoethyltrimethoxysilane, and γ-mercaptopropyltrimethoxysilane; the hydrophobic silane is one or more of perfluorooctyltriethoxysilane, perfluorohexyltriethoxysilane, perfluorodecyltriethoxysilane, 11-chloroundecyltriethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, and triethoxyoctylsilane; the volume ratio of anhydrous ethanol, deionized water, and silane is 90:5:5; the concentration of zinc trifluoromethanesulfonate is 0.05 mol L -1 ~0.5mol L -1 .
[0020] Preferably, the power of the spraying device is 2 to 10 W; the spraying time is 0.2 to 5 s cm -2 .
[0021] More preferably, the zinc-philic silane is γ-aminopropyltriethoxysilane; the hydrophobic silane is perfluorooctyltriethoxysilane; and the concentration of zinc trifluoromethanesulfonate is 0.15 mol L -1 ; The power of the spraying device is 5W; the spraying time is 2s cm -2 .
[0022] A dual-function negative electrode modifier for a zinc ion battery, comprising the modifier liquid A and liquid B described in the present invention.
[0023] An application of a zinc ion battery modifier, wherein the application uses a spraying device with a power of 2 to 10 W to spray the modifier liquid A and liquid B of the invention on the surface of a zinc negative electrode in sequence, and the spraying time is 0.1 to 5 s cm -2 .
[0024] A zinc negative electrode with an artificial double-modified layer is provided, wherein the zinc negative electrode is obtained by the modification method of the present invention, or is obtained by chemically modifying the modifier of the present invention, or is prepared by applying the modifier of the present invention.
[0025] A zinc ion battery, wherein the negative electrode of the battery is the zinc negative electrode with an artificial double-modified layer described in the present invention.
[0026] Beneficial Effects
[0027] (1) The present invention provides a method for modifying the negative electrode of a zinc ion battery. Since the method contains the negative electrode modifier of the present invention, the method can be used to modify the zinc negative electrode, which can have the dual functions of zinc affinity and hydrophobicity, and has the dual functions of regulating the zinc ion deposition flux and controlling the desolvation of hydrated zinc ions, thereby improving the cycle life and working performance of the zinc ion battery. In the application of electrodes or batteries, the artificial SEI film formed can be made uniform and dense, so that the battery can have a stable long-term cycle and good electrochemical performance.
[0028] (2) The present invention provides a negative electrode modifier for zinc ion batteries, wherein two silanes with different substituents in the modifier both reach a hydrolysis-alcoholysis equilibrium in a mixed solution of water and ethanol after stirring:
[0029]
[0030] In the formula, the hydrolysis process is from left to right, and the alcoholysis process is from right to left; R is the corresponding zinc-philic or hydrophobic substituent. -1 Zinc trifluoromethanesulfonate is used to construct a conductive network in the double-layer silane modification layer to improve the ionic conductivity of the modification layer. After stirring, the zinc foil is modified with two modifiers, A and B, which can sequentially generate zinc-philic and hydrophobic dense SEI films on the surface of the zinc foil, inhibit the occurrence of hydrogen evolution reaction, and regulate the uniform deposition of zinc, which not only inhibits the growth of zinc dendrites, improves the cycle life of zinc-ion batteries, but also improves the electrochemical performance of batteries.
[0031] (3) The present invention provides an application of a zinc ion battery negative electrode modifier. The spraying method used in the application is simple and easy, and the thickness is adjustable, so it is easy to obtain a flat and dense zinc negative electrode modification layer. At the same time, the low thickness of the modification layer can avoid the slowdown of reaction kinetics caused by a thick modification layer caused by scraping, brushing, etc.
[0032] (4) The present invention provides a zinc negative electrode with an artificial SEI film, wherein the surface of the zinc negative electrode is composed of a zinc-philic silane modification layer and a hydrophobic silane modification layer from the inside to the outside, and the film-forming conditions have a certain degree of controllability; and the application is that before the electrochemical cycle, the zinc electrode body is pre-reacted with the modification solution of the present invention, that is, the SEI film is prefabricated on the surface of the zinc negative electrode body in advance, thereby obtaining a zinc negative electrode with a SEI film, and then the electrode is applied to a zinc ion battery, thereby reducing the consumption of additive molecules during the cycle, and being more conducive to the dual role of regulating the zinc ion deposition flux and promoting the desolvation of hydrated zinc ions.
[0033] (5) The present invention provides a zinc ion battery, wherein the zinc negative electrode of the battery has relatively uniform zinc ion deposition during the cycle, and the growth of zinc dendrites is suppressed, thereby improving the cycle performance of the battery and enabling the electrochemical performance to be stably exerted at a high level; the assembled zinc-zinc symmetric battery has a small polarization, and matching with the vanadium dioxide positive electrode can achieve a higher specific capacity, which is beneficial to stably improving the cycle life of the zinc ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The Zn||Zn symmetric battery assembled from the experimental group (denoted as NF@Zn) and the control group (denoted as Bare Zn) in Test Example 1 was tested at 1 mA cm -2 , 1mAh cm -2 The following is the cycle test result diagram.
[0035] Figure 2 The Zn||Zn symmetric battery assembled from the experimental group (denoted as NF@Zn) and the control group (denoted as Bare Zn) in Test Example 2 was tested at 5 mA cm -2 , 1mAh cm -2 The following is the cycle test result diagram.
[0036] Figure 3 The Zn||Cu half-cells assembled from the experimental group (denoted as NF@Zn) and the control group (denoted as Bare Zn) in Test Example 1 were tested at 1 mA cm -2 , 1mAh cm -2 The following is the cycle test result diagram.
[0037] Figure 4The Zn||VO2 full battery assembled from the experimental group (denoted as NF@Zn) and the control group (denoted as Bare Zn) in Test Example 1 was tested at 3C (1C = 400 mAh g -1 ) under the cycle test results.
[0038] Figure 5 The deposition capacities of different samples in test example 1 (0.2, 0.5, 1.0 mAh cm -2 ) under modified (denoted as NF@Zn) and unmodified (denoted as Bare Zn) Zn deposition SEM images of negative electrodes: (a)-(c) modified zinc foil; (d)-(f) unmodified zinc foil.
[0039] Figure 6 These are the SEM images of the negative electrode of the Zn||Zn symmetric battery using modified (denoted as NF@Zn) and unmodified (denoted as Bare Zn) negative electrodes in Test Example 1 after 10 cycles: (a)-(c) modified zinc foil; (d)-(f) unmodified zinc foil.
[0040] Figure 7 The Zn||Zn symmetric battery with modified (denoted as NF@Zn) and unmodified (denoted as Bare Zn) anodes in Test Example 1 was tested at a current density of 5 mA cm -2 Optical images of the tests performed under in situ optical microscopy conditions. DETAILED DESCRIPTION
[0041] The present invention is further described below in conjunction with specific embodiments, wherein the methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels or prepared according to literature unless otherwise specified.
[0042] Example 1
[0043] A zinc ion battery negative electrode, the preparation method of which is as follows:
[0044] (1) Prepare 10 mL of silane modification solution A and B (A: 90% anhydrous ethanol + 5% deionized water + 5% 3-aminopropyltriethoxysilane + 0.15 mol L -1 Zinc trifluoromethanesulfonate; B: 90% anhydrous ethanol + 5% deionized water + 5% perfluorooctyl triethoxysilane + 0.15mol L -1 Zinc trifluoromethanesulfonate, the substance contents are all volume fractions), and stirred with a magnetic stirrer for 6 hours.
[0045] (2) Cut the zinc foil into appropriate sizes, clean it with detergent, deionized water, and anhydrous ethanol in sequence, and place it in a 5 mol / L -1Ultrasonicate in dilute hydrochloric acid of concentration for 1 minute to remove the oxide layer on the surface, then use deionized water and anhydrous ethanol to clean the residual hydrochloric acid on the surface, and dry it for later use. After the modification solution in (1) is stirred, immediately use a 5W handheld electrosprayer to spray the two modification solutions A and B on the zinc foil in turn to form a dual-functional coating. For a 5cm×4cm zinc foil, each modification solution is sprayed for 40 seconds. After each coating is sprayed, dry it at room temperature for 0.5h. After the two layers are sprayed, place the zinc sheet in a vacuum drying oven and dry it at 80℃ for 6h to solidify it. The zinc sheets with modified layers on the surface are cut into discs with a diameter of Φ=11mm to complete the preparation of the negative electrode sheet.
[0046] Example 2
[0047] A zinc ion battery negative electrode, the preparation method of which is as follows:
[0048] (1) Prepare 10 mL of silane modification solution A and B (A: 90% anhydrous ethanol + 5% deionized water + 5% γ-aminopropylmethyldiethoxysilane + 0.15 mol L -1 Zinc trifluoromethanesulfonate; B: 90% anhydrous ethanol + 5% deionized water + 5% perfluorooctyl triethoxysilane + 0.15mol L -1 Zinc trifluoromethanesulfonate, the substance contents are all volume fractions), and stirred with a magnetic stirrer for 6 hours.
[0049] (2) Cut the zinc foil into appropriate sizes, clean it with detergent, deionized water, and anhydrous ethanol in sequence, and place it in a 5 mol / L -1 Ultrasonicate in dilute hydrochloric acid of concentration for 1 minute to remove the oxide layer on the surface, then use deionized water and anhydrous ethanol to clean the residual hydrochloric acid on the surface, and dry it for later use. After the modification solution in (1) is stirred, immediately use a 5W handheld electrosprayer to spray the two modification solutions A and B on the zinc foil in turn to form a dual-functional coating. For a 5cm×4cm zinc foil, each modification solution is sprayed for 40 seconds. After each coating is sprayed, dry it at room temperature for 0.5h. After the two layers are sprayed, place the zinc sheet in a vacuum drying oven and dry it at 80℃ for 6h to solidify it. The zinc sheets with modified layers on the surface are cut into discs with a diameter of Φ=11mm to complete the preparation of the negative electrode sheet.
[0050] Example 3
[0051] A zinc ion battery negative electrode, the preparation method of which is as follows:
[0052] (1) Prepare 10 mL of silane modification solution A and B (A: 90% anhydrous ethanol + 5% deionized water + 5% 3-aminopropyltriethoxysilane + 0.15 mol L -1Zinc trifluoromethanesulfonate; B: 90% anhydrous ethanol + 5% deionized water + 5% perfluorohexyltriethoxysilane + 0.15mol L -1 Zinc trifluoromethanesulfonate, the substance contents are all volume fractions), and stirred with a magnetic stirrer for 6 hours.
[0053] (2) Cut the zinc foil into appropriate sizes, clean it with detergent, deionized water, and anhydrous ethanol in sequence, and place it in a 5 mol / L -1 Ultrasonicate in dilute hydrochloric acid of concentration for 1 minute to remove the oxide layer on the surface, then use deionized water and anhydrous ethanol to clean the residual hydrochloric acid on the surface, and dry it for later use. After the modification solution in (1) is stirred, immediately use a 5W handheld electrosprayer to spray the two modification solutions A and B on the zinc foil in turn to form a dual-functional coating. For a 5cm×4cm zinc foil, each modification solution is sprayed for 40 seconds. After each coating is sprayed, dry it at room temperature for 0.5h. After the two layers are sprayed, place the zinc sheet in a vacuum drying oven and dry it at 80℃ for 6h to solidify it. The zinc sheets with modified layers on the surface are cut into discs with a diameter of Φ=11mm to complete the preparation of the negative electrode sheet.
[0054] Example 4
[0055] A zinc ion battery negative electrode, the preparation method of which is as follows:
[0056] (1) Prepare 10 mL of silane modification solution A and B (A: 90% anhydrous ethanol + 5% deionized water + 5% 3-aminopropyltriethoxysilane + 0.15 mol L -1 Zinc trifluoromethanesulfonate; B: 90% anhydrous ethanol + 5% deionized water + 5% perfluorooctyl triethoxysilane + 0.15mol L -1 Zinc trifluoromethanesulfonate, the substance contents are all volume fractions), and stirred with a magnetic stirrer for 6 hours.
[0057] (2) Cut the zinc foil into appropriate sizes, clean it with detergent, deionized water, and anhydrous ethanol in sequence, and place it in a 5 mol / L -1 Ultrasonicate in dilute hydrochloric acid of concentration for 1 minute to remove the oxide layer on the surface, then use deionized water and anhydrous ethanol to clean the residual hydrochloric acid on the surface, and dry it for later use. After the modification solution in (1) is stirred, immediately use a 5W handheld electrosprayer to spray the two modification solutions A and B on the zinc foil in turn to form a dual-functional coating. For a 5cm×4cm zinc foil, each modification solution is sprayed for 30 seconds. After each coating is sprayed, dry it at room temperature for 0.5h. After the two layers are sprayed, place the zinc sheet in a vacuum drying oven and dry it at 80℃ for 6h to solidify it. The zinc sheets with modified layers on the surface are cut into discs with a diameter of Φ=11mm to complete the preparation of the negative electrode.
[0058] Example 5
[0059] A zinc ion battery negative electrode, the preparation method of which is as follows:
[0060] (1) Prepare 10 mL of silane modification solution A and B (A: 90% anhydrous ethanol + 5% deionized water + 5% 3-aminopropyltriethoxysilane + 0.15 mol L -1 Zinc trifluoromethanesulfonate; B: 90% anhydrous ethanol + 5% deionized water + 5% perfluorooctyl triethoxysilane + 0.15mol L -1 Zinc trifluoromethanesulfonate, the substance contents are all volume fractions), and stirred with a magnetic stirrer for 6 hours.
[0061] (2) Cut the zinc foil into appropriate sizes, clean it with detergent, deionized water, and anhydrous ethanol in sequence, and place it in a 5 mol / L -1 Ultrasonicate in dilute hydrochloric acid of concentration for 1 minute to remove the oxide layer on the surface, then use deionized water and anhydrous ethanol to clean the residual hydrochloric acid on the surface, and dry it for later use. After the modification solution in (1) is stirred, immediately use a 5W handheld electrosprayer to spray modification solutions A and B on the zinc foil in turn to form a dual-functional coating. For a 5cm×4cm zinc foil, spray modification solution A for 40s and modification solution B for 20s. After each coating is sprayed, dry it at room temperature for 0.5h. After both layers are sprayed, place the zinc sheet in a vacuum drying oven and dry it at 80℃ for 6h to solidify it. Cut the zinc sheet with a modified layer on the surface into discs with a diameter of Φ=11mm to complete the preparation of the negative electrode sheet.
[0062] Example 6
[0063] A zinc ion battery negative electrode, the preparation method of which is as follows:
[0064] (1) Prepare 10 mL of silane modification solution A and B (A: 90% anhydrous ethanol + 5% deionized water + 5% 3-aminopropyltriethoxysilane + 0.15 mol L -1 Zinc trifluoromethanesulfonate; B: 90% anhydrous ethanol + 5% deionized water + 5% perfluorooctyl triethoxysilane + 0.15mol L -1 Zinc trifluoromethanesulfonate, the substance contents are all volume fractions), and stirred with a magnetic stirrer for 6 hours.
[0065] (2) Cut the zinc foil into appropriate sizes, clean it with detergent, deionized water, and anhydrous ethanol in sequence, and place it in a 5 mol / L -1Ultrasonicate in dilute hydrochloric acid of concentration for 1 minute to remove the oxide layer on the surface, then use deionized water and anhydrous ethanol to clean the residual hydrochloric acid on the surface, and dry it for later use. After the modification solution in (1) is stirred, immediately use a 5W handheld electrosprayer to spray modification solutions A and B on the zinc foil in turn to form a dual-functional coating. For a 5cm×4cm zinc foil, spray modification solution A for 20s and modification solution B for 40s. After each coating is sprayed, dry it at room temperature for 0.5h. After both layers are sprayed, place the zinc sheet in a vacuum drying oven and dry it at 80℃ for 6h to solidify it. The zinc sheets with modified layers on the surface are cut into discs with a diameter of Φ=11mm to complete the preparation of the negative electrode sheet.
[0066] Example 7
[0067] A zinc ion battery negative electrode, the preparation method of which is as follows:
[0068] (1) Prepare 10 mL of silane modification solution A and B (A: 90% anhydrous ethanol + 5% deionized water + 5% 3-aminopropyltriethoxysilane + 0.15 mol L -1 Zinc trifluoromethanesulfonate; B: 90% anhydrous ethanol + 5% deionized water + 5% perfluorooctyl triethoxysilane + 0.15mol L -1 Zinc trifluoromethanesulfonate, the substance contents are all volume fractions), and stirred with a magnetic stirrer for 6 hours.
[0069] (2) Cut the zinc foil into appropriate sizes, clean it with detergent, deionized water, and anhydrous ethanol in sequence, and place it in a 5 mol / L -1 Ultrasonicate in dilute hydrochloric acid of concentration for 1 minute to remove the oxide layer on the surface, then use deionized water and anhydrous ethanol to clean the residual hydrochloric acid on the surface, and dry it for later use. After the modification solution in (1) is stirred, immediately use a 10W handheld electrosprayer to spray the two modification solutions A and B on the zinc foil in turn to form a dual-functional coating. For a 5cm×4cm zinc foil, each modification solution is sprayed for 40s. After each coating is sprayed, dry it at room temperature for 0.5h. After the two layers are sprayed, place the zinc sheet in a vacuum drying oven and dry it at 80℃ for 6h to solidify it. The zinc sheets with modified layers on the surface are cut into discs with a diameter of Φ=11mm to complete the preparation of the negative electrode sheet.
[0070] Example 8
[0071] A zinc ion battery negative electrode, the preparation method of which is as follows:
[0072] (1) Prepare 10 mL of silane modification solution A and B (A: 90% anhydrous ethanol + 5% deionized water + 5% 3-aminopropyltriethoxysilane + 0.1 mol L -1Zinc trifluoromethanesulfonate; B: 90% anhydrous ethanol + 5% deionized water + 5% perfluorooctyl triethoxysilane + 0.1 mol L -1 Zinc trifluoromethanesulfonate, the substance contents are all volume fractions), and stirred with a magnetic stirrer for 6 hours.
[0073] (2) Cut the zinc foil into appropriate sizes, clean it with detergent, deionized water, and anhydrous ethanol in sequence, and place it in a 5 mol / L -1 Ultrasonicate in dilute hydrochloric acid of concentration for 1 minute to remove the oxide layer on the surface, then use deionized water and anhydrous ethanol to clean the residual hydrochloric acid on the surface, and dry it for later use. After the modification solution in (1) is stirred, immediately use a 5W handheld electrosprayer to spray the two modification solutions A and B on the zinc foil in turn to form a dual-functional coating. For a 5cm×4cm zinc foil, each modification solution is sprayed for 40 seconds. After each coating is sprayed, dry it at room temperature for 0.5h. After the two layers are sprayed, place the zinc sheet in a vacuum drying oven and dry it at 80℃ for 6h to solidify it. The zinc sheets with modified layers on the surface are cut into discs with a diameter of Φ=11mm to complete the preparation of the negative electrode sheet.
[0074] Example 9
[0075] A zinc ion battery negative electrode modifier, the preparation method of which is as follows:
[0076] Prepare 10 mL of silane modification solution A and B (A: 90% anhydrous ethanol + 5% deionized water + 5% 3-aminopropyltriethoxysilane + 0.15 mol L -1 Zinc trifluoromethanesulfonate; B: 90% anhydrous ethanol + 5% deionized water + 5% perfluorooctyl triethoxysilane + 0.15mol L -1 Zinc trifluoromethanesulfonate, the substance contents are all volume fractions), and stirred for 6 hours using a magnetic stirrer to obtain a zinc ion battery negative electrode modifier having zinc-philic silane and hydrophobic silane that can be used in combination.
[0077] Test Example 1
[0078] The zinc foil and glass fiber diaphragm prepared in Example 1, 2 mol L -1 ZnSO4 electrolyte was assembled into a button symmetrical battery (denoted as NF@Zn);
[0079] Bare zinc foil and glass fiber diaphragm, 2 mol L -1 ZnSO4 electrolyte was assembled into a button symmetrical cell (denoted as BareZn);
[0080] The assembly order of the button symmetrical batteries in the experimental group and the control group is: positive electrode shell, zinc sheet, 150 μL electrolyte, diaphragm, zinc sheet, stainless steel gasket, stainless steel spring and negative electrode shell; after assembly, the battery is pressed using a punch. -2 , with a capacity of 1 mAh cm -2 The charge and discharge test was carried out under the following conditions, and the test results were as follows Figure 1 shown.
[0081] Depend on Figure 1 It can be seen that after about 200 hours of cycling, the voltage of the symmetrical battery assembled with pure zinc drops sharply. This is because the growth of zinc dendrites allows electrons to tunnel from the top of the zinc dendrites at one pole to the top of the zinc dendrites at the other pole, which means a soft short circuit occurs. The modified NF@Zn exhibits a stable long-cycle performance of more than 1000 hours, with an overpotential of only 31mV, showing stable long-cycle performance.
[0082] Test Example 2
[0083] The zinc foil and glass fiber diaphragm prepared in Example 2, 2 mol L -1 ZnSO4 electrolyte was assembled into a button symmetrical battery (denoted as NF@Zn);
[0084] Bare zinc foil and glass fiber diaphragm, 2 mol L -1 ZnSO4 electrolyte was assembled into a button symmetrical cell (denoted as BareZn);
[0085] The assembly order of the button symmetrical batteries in the experimental group and the control group is: positive electrode shell, zinc sheet, 150 μL electrolyte, diaphragm, zinc sheet, stainless steel gasket, stainless steel spring and negative electrode shell; after assembly, the battery is pressed using a punch. -2 , with a capacity of 1 mAh cm -2 The charge and discharge test was carried out under the following conditions, and the test results were as follows Figure 2 shown.
[0086] Depend on Figure 2 It can be seen that at a current density of 5 mAh cm -2 , with a deposition / stripping capacity of 1 mAh cm -2Under the cycling conditions of , the voltage of the symmetrical battery assembled with bare zinc increased rapidly at 340 h, and then showed an unstable voltage spike. The short circuit of the bare zinc negative electrode at high current density is attributed to the increase in current density, which increases the polarization of the symmetrical battery assembled with bare zinc, slows down the kinetics, makes the electric field on the surface of the zinc negative electrode uneven, and reduces the uniformity of zinc deposition, resulting in overpotential fluctuations and "hard short circuit". In contrast, even at high current density, the zinc negative electrode of the experimental group still shows extraordinary electrochemical cycling stability. At a current density of 5 mAh cm -2 , with a deposition / stripping capacity of 1 mAh cm -2 Under the condition of 1000 h, the overpotential is 99 mV, and the stable cycle is 1000 h. This shows that the modification of NF@Zn in the experimental group improves the battery stability.
[0087] Test Example 3
[0088] The zinc foil and glass fiber diaphragm prepared in Example 1, 2 mol L -1 ZnSO4 electrolyte and copper foil were assembled into a button half-cell (denoted as NF@Zn);
[0089] Bare zinc foil and glass fiber diaphragm, 2 mol L -1 ZnSO4 electrolyte and copper foil were assembled into a button half-cell (denoted as Bare Zn);
[0090] The assembly order of the button half-cells in the experimental group and the control group is: positive electrode shell, copper foil, 150 μL electrolyte, diaphragm, zinc sheet, stainless steel gasket, stainless steel spring and negative electrode shell; after assembly, the battery is pressed using a punch. -2 , with a capacity of 1 mAh cm -2 The charge and discharge test was carried out under the following conditions, and the test results were as follows Figure 3 shown.
[0091] Depend on Figure 3 It can be seen that at a current density of 1 mA cm -2 , the deposition capacity is 1 mAh cm -2 Under the conditions of , the coulombic efficiency of the bare zinc in the control group fluctuated violently at about 60 weeks; while the half-cell assembled with the double-layer modified copper foil could stably cycle for nearly 1000 cycles (about 2000h), and its coulombic efficiency reached 99.89%, demonstrating the extraordinary effect of the zinc-philic-hydrophobic double-layer silane design in homogenizing the zinc ion flux and promoting uniform zinc ion deposition. The electrochemical cycle test results of the half-cell show the ability of the modified layer to inhibit dendrite formation and maintain good electrochemical performance of the half-cell.
[0092] Test Example 4
[0093] The zinc foil and glass fiber diaphragm prepared in Example 1, 2 mol L -1 ZnSO4 electrolyte and VO2 positive electrode are assembled into a button full battery (denoted as NF@Zn);
[0094] Bare zinc foil and glass fiber diaphragm, 2 mol L -1 ZnSO4 electrolyte and VO2 positive electrode are assembled into a button full battery (denoted as Bare Zn);
[0095] The VO2 positive electrode plate is a plate obtained by coating and drying a commercially available VO2 material: polytetrafluoroethylene: conductive carbon black in a ratio of 6:2:2, and the surface load is about 6-8 mg cm -2 .
[0096] The assembly order of the button cells in the experimental and control groups is: positive electrode shell, VO2 positive electrode sheet, 150μL electrolyte, diaphragm, zinc sheet, stainless steel gasket, stainless steel spring and negative electrode shell; after assembly, the battery is pressed using a punch. -1 ) to carry out charge and discharge test, and the test results are as follows Figure 4 shown.
[0097] Depend on Figure 4 It can be seen that compared with the control group full battery which can only maintain less than 400 cycles, the experimental group NF@Zn still maintains 142mAh g after about 2000 cycles. -1 The cycling performance of the full cell is consistent with that of the half cell, which together demonstrates that the modified zinc anode has great potential in inhibiting dendrite growth, maintaining high specific capacity and coulombic efficiency of the battery, and extending the service life of the battery.
[0098] In addition, if Figure 5-Figure 6 As shown in Figure 2, various characterization test results such as scanning electron microscopy show that the zinc deposited on the modified anode (NF@Zn) has a high conductivity at 0.2, 0.5 and 1 mA cm -2 At various deposition capacities and after 10 weeks of electrochemical cycling, it is still smooth and dense, with no obvious dendrite growth. It can be seen that the hexagonal deposition morphology corresponds to the deposition parallel to the (002) crystal plane. The deposition is uniform and the deposition performance is good, which is conducive to the long cycle performance of the battery. At the same current density and deposition capacity, there is obvious dendrite growth perpendicular and oblique to the zinc substrate on the unmodified negative electrode (Bare Zn), showing that the dominant crystal planes of its growth are (100) and (101) crystal planes. Zinc metal has a high Young's modulus, and the growth mode that is not parallel to the surface of the zinc foil substrate can easily cause dendrites to pierce the diaphragm and cause a short circuit in the battery. In contrast, the deposition of modified negative electrode zinc still tends to be smooth and dense, which is conducive to long and stable battery cycling. Figure 7The optical microscope shown can more intuitively show the superior parallel deposition morphology of the zinc negative electrode (NF@Zn) prepared in Example 1, while the zinc negative electrode (Bare Zn) in the control group shows an uneven deposition morphology. Based on the above characterization test results, it can be seen that the zinc negative electrode prepared in Example 1 can have the dual functions of zinc affinity and hydrophobicity, and has the dual functions of regulating the zinc ion deposition flux and controlling the desolvation of hydrated zinc ions, thereby improving the cycle life and working performance of zinc ion batteries. In the application of electrodes or batteries, the artificial SEI film formed can be made uniform and dense, so that the battery can have a stable long-term cycle, avoid the capacity decay of zinc ion batteries, and show excellent electrochemical performance.
[0099] The zinc negative electrodes provided in other embodiments were tested with reference to the above method. Compared with the unmodified electrolyte or electrode, the zinc negative electrodes showed an inhibitory effect on the hydrogen evolution reaction, a regulatory effect on the zinc ion deposition flux, better cycle stability, and improved coulombic efficiency. This further illustrates the effect of the zinc-philic-hydrophobic double-layer silane-modified zinc negative electrode proposed in the present invention on improving the battery cycle performance, and the significant effect of inhibiting the dendrite growth and hydrogen evolution reaction of zinc ion batteries.
[0100] The present invention includes but is not limited to the above embodiments. Any equivalent replacement or partial improvement made under the principle of the spirit of the present invention shall be deemed to be within the protection scope of the present invention.
Claims
1. A method for modifying a negative electrode of a zinc ion battery, characterized in that: The method steps are as follows: (1) preparing modification solution A: anhydrous ethanol + deionized water + zincophilic silane + zinc trifluoromethanesulfonate; B: anhydrous ethanol + deionized water + hydrophobic silane + zinc trifluoromethanesulfonate, and magnetically stirring the mixed modification solutions A and B for 6 hours to obtain a uniform solution; (2) Liquid A and Liquid B are sprayed onto the pretreated zinc negative electrode surface in sequence. After each coating is sprayed, it is dried at room temperature for 30 minutes and then dried in a high-temperature drying oven for 6 hours.
2. A zinc ion battery negative electrode modification method according to claim 1, characterized in that: The zinc-philic silane in (1) is one or more of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-aminopropylmethyldiethoxysilane, β-cyanoethyltriethoxysilane, γ-cyanoethyltrimethoxysilane, and γ-mercaptopropyltrimethoxysilane; the hydrophobic silane is one or more of perfluorooctyltriethoxysilane, perfluorohexyltriethoxysilane, perfluorodecyltriethoxysilane, 11-chloroundecyltriethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, and triethoxyoctylsilane; the volume ratio of anhydrous ethanol, deionized water, and silane is 90:5:5; the concentration of zinc trifluoromethanesulfonate is 0.05 mol L -1 ~0.5mol L -1 .
3. A method for modifying the negative electrode of a zinc ion battery according to claim 1-2, characterized in that: The power of the spraying device is 2 to 10W; the spraying time is 0.2 to 5s cm -2 .
4. A zinc ion battery bifunctional negative electrode modifier, characterized in that: The negative electrode modifier comprises the modifier liquid A and liquid B as described in claim 1.
5. An application of a zinc ion battery modifier as claimed in any one of claims 2 to 4, characterized in that: Use a spraying device with a power of 2 to 10 W to spray the modifier liquid A and liquid B described in claim 1 on the surface of the zinc negative electrode in sequence, and the spraying time is 0.1 to 5 s cm -2 .
6. A zinc negative electrode with an artificial double-modified layer, characterized in that: The zinc negative electrode is a zinc negative electrode obtained by the modification method described in any one of claims 1 to 3, or a zinc negative electrode chemically modified by the modifier described in claim 4, or a zinc negative electrode prepared by using the modifier described in claim 5.
7. A zinc ion battery, characterized in that: The negative electrode of the battery is the zinc negative electrode with an artificial double-modified layer as claimed in claim 6.
Citation Information
Patent Citations
Organic zinc phosphate-silane composite passive film modified zinc metal negative electrode and preparation method and application thereof
CN113690401A
Zinc metal negative electrode with amino silane polymer protective layer and preparation method of zinc metal negative electrode
CN114843431A
Zinc negative electrode with stress response interface modification layer, preparation method and zinc ion battery
CN116470013A
Alkaline battery
JP1990174067A
Anode active material and lithium secondary battery comprising the same
KR1020130116803A
Cited By
Hydrophobic-zinc-philic interface protection layer of high-magnification zinc metal negative electrode as well as preparation and application of hydrophobic-zinc-philic interface protection layer
CN120388990A
